Efferocytosis by macrophages in physiological and pathological conditions: regulatory pathways and molecular mechanisms - Sheng, Yan−Ran; Hu, Wen−Ting; Chen, Siman; Zhu, Xiao−Yong (Frontiers in Immunology, 2024)
Efferocytosis is defined as the highly effective phagocytic removal of apoptotic cells (ACs) by professional or non-professional phagocytes. Tissue-resident professional phagocytes (“efferocytes”), such as macrophages, have high phagocytic capacity and are crucial to resolve inflammation and aid in homeostasis. Recently, numerous exciting discoveries have revealed divergent (and even diametrically opposite) findings regarding metabolic immune reprogramming associated with efferocytosis by macrophages. In this review, we highlight the key metabolites involved in the three phases of efferocytosis and immune reprogramming of macrophages under physiological and pathological conditions. The next decade is expected to yield further breakthroughs in the regulatory pathways and molecular mechanisms connecting immunological outcomes to metabolic cues as well as avenues for “personalized” therapeutic intervention.